Bilateral Post Fever Retinitis With Retinal Vascular Occlusions Following Severe Acute Respiratory Syndrome Corona Virus (SARS-CoV2) Infection. (17th November 2022) - Mahendradas, Padmamalini; Hande, Prathibha; Patil, Aditya; Kawali, Ankush; Sanjay, Srinivasan; Ahmed, Syed Asrar; Thomas, Sherina; Shetty, Rohit
ABSTRACT: Introduction: As the world fights the pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), several reports of retinal manifestations of the disease are emerging. Post fever retinitis is a well reported ocular inflammatory reaction to multiple invasive agents, be it virus, bacteria or other microbial agent. Purpose: We report an interesting case of bilateral multifocal retinitis with multiple vascular occlusions in a patient, three weeks after a febrile illness. Results: Investigations to ascertain the cause of fever resulted in identifying ephemeral seropositivity for several different Ribonucleic acid (RNA) viruses. The retinitis was managed with systemic steroids, doxycycline and anticoagulants with improvement in vision. Conclusion: High and persistent seropositive response against (SARS-CoV-2) helped us to narrow it as the causative agent but the cross reactivity of SARS-CoV-2 with other viruses can be misleading and needs careful interpretation.